2006
DOI: 10.1111/j.1574-6968.2006.00448.x
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Gram-positive poly(3-hydroxybutyrate) (PHB)-degrading bacterium from compost, and cloning and characterization of a gene encoding PHB depolymerase ofBacillus megateriumN-18-25-9

Abstract: A Gram-positive poly(3-hydroxybutyrate) (PHB)-degrading bacterial strain was isolated from compost. This organism, identified as Bacillus megaterium N-18-25-9, produced a clearing zone on opaque NB-PHB agar, indicating the presence of extracellular PHB depolymerase. A PHB depolymerase gene, PhaZ(Bm), of B. megaterium N-18-25-9 was cloned and sequenced, and the recombinant gene product was purified from Escherichia coli. The N-terminal half region of PhaZ(Bm) shared significant homologies with a catalytic domai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
25
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(26 citation statements)
references
References 19 publications
1
25
0
Order By: Relevance
“…Its enzyme activity was not increased by the addition of 1 mM CaCl 2 to the reaction mixture and was not inhibited by the presence of 10 mM EDTA, suggesting that the calcium ion is not required as a cofactor for the enzyme activity. This is in striking contrast to the B. megaterium N-18-25-9 PhaZ (37). To analyze the dPHB-binding ability of PhaZ, the mature form of PhaZ was pretreated with 1 mM PMSF to inhibit the dPHB-degrading activity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Its enzyme activity was not increased by the addition of 1 mM CaCl 2 to the reaction mixture and was not inhibited by the presence of 10 mM EDTA, suggesting that the calcium ion is not required as a cofactor for the enzyme activity. This is in striking contrast to the B. megaterium N-18-25-9 PhaZ (37). To analyze the dPHB-binding ability of PhaZ, the mature form of PhaZ was pretreated with 1 mM PMSF to inhibit the dPHB-degrading activity.…”
Section: Resultsmentioning
confidence: 99%
“…NRRL B-14911 has been partially determined and is available from GenBank. It encodes a putative PHB depolymerase (GenBank accession number ZP_01169502) of 592 amino acids (see Discussion) that shows 53% identity and 68% similarity to the extracellular PHB depolymerase of B. megaterium N-18-25-9 (590 amino acids; BAF35850) (37). The analysis of the putative PhaZ of Bacillus sp.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, maximum production of PHB depolymerase by A, fumigates was observed at pH 7 after 24 h of incubation in liquid medium (Lodhi et al, 2011). The maximum activity of extracellular PHB depolymerase produced by Bacillus megaterium N-18-25-9, was observed at pH 9.0 at 65ºC (Takaku et al, 2006) and at pH 7.5-8.0 when sewage sludge was used as inoculum (Briese et al, 1994). In the present study, the maximum production of PHB depolymerase was found at 0.3% of substrate concentration as indicated by the maximum enzyme activity, while it decreased with further increase in polymer concentration which might be due to substrate level inhibition (Manna and Paul, 2000).…”
Section: Discussionmentioning
confidence: 96%
“…Composting is a high-temperature process; hence, thermophilic microbes capable of degrading various kinds of polyesters are of interest (Takeda et al 1998;Romen et al 2004, Takaku et al 2006. Actinomycetes capable of PHA degradation at high temperature, especially poly[(R)-3-hydroxybutyrate] (PHB) Polyhydroxyalkanoate degradation by a Streptomyces sp.…”
Section: Introductionmentioning
confidence: 99%